2015
DOI: 10.1002/anie.201503304
|View full text |Cite
|
Sign up to set email alerts
|

An Aluminum Hydride That Functions like a Transition‐Metal Catalyst

Abstract: The reaction of [LAlH2 ] (L=HC(CMeNAr)2 , Ar=2,6-iPr2 C6 H3 ) with MeOTf (Tf=SO2 CF3 ) resulted in the formation of [LAlH(OTf)] (1) in high yield. The triflate substituent in 1 increases the positive charge at the aluminum center, which implies that 1 has a strong Lewis acidic character. The excellent catalytic activity of 1 for the hydroboration of organic compounds with carbonyl groups was investigated. Furthermore, it was shown that 1 effectively initiates the addition reaction of trimethylsilyl cyanide (TM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
157
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(167 citation statements)
references
References 38 publications
7
157
1
2
Order By: Relevance
“…We embarked on extending the main‐group chemistry, fired by the ubiquitous β‐diketiminate ligand and its derivatives, to related bis(heterocyclo)methane and amine ligand systems. Starting from dipyridylmethane and ‐methanides ( A in Scheme ) we extended the ligand class to the dipyridylamides, ‐phosphanides, and ‐arsenides ( B ) .…”
Section: Introductionmentioning
confidence: 99%
“…We embarked on extending the main‐group chemistry, fired by the ubiquitous β‐diketiminate ligand and its derivatives, to related bis(heterocyclo)methane and amine ligand systems. Starting from dipyridylmethane and ‐methanides ( A in Scheme ) we extended the ligand class to the dipyridylamides, ‐phosphanides, and ‐arsenides ( B ) .…”
Section: Introductionmentioning
confidence: 99%
“…[23] Also the last s-bond metathesis step in the cycle seemed questionable.Acomprehensive calculational study, however, demonstrated that the metal hydride mechanism shown in Scheme 1isfeasible. [15,18,[31][32][33][34][35][36][37][38][39][40][41][42] Especially noteworthy are two very recent investigations on LiAlH 4 -catalyzed alkene and aldehyde/ketone hydroboration. Acrucial step is the hydrogenolysis of the metal À Cbond by H 2 ,for which the rate is known to decrease with decreasing bond ionicity:N a À C > Mg À C > Al À C. [25] since it is well-known that RNH 2 and R 2 NH react smoothly with LiAlH 4 to give aluminium amide products and H 2 , [26][27][28][29][30][31] hydrogenolysis of AlÀNbonds to give amines is anticipated to be even more cumbersome.S ubstitution of H 2 for polar borane or silane reductants was therefore al ogical step.…”
mentioning
confidence: 99%
“…Roesky and coworkers demonstrated that a b-diketiminato stabilised aluminium hydride complex is an excellent catalyst for hydroboration of alkynes and carbonyl groups. [5] More recently, Cowley, Thomas and Bismuto revealed that DIBAL(H), and Et 3 Al·DABCO can catalyse hydroboration of alkynes. [6] Our groups interests lie in exploiting the synergistic reactivity imparted by two distinct metal centres [7,8] installed within a bimetallic complex.…”
mentioning
confidence: 99%